1999
DOI: 10.1039/a809935i
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical calculations on the structures, electronic and magnetic properties of binary 3d transition metal nitrides

Abstract: The electronic structures of a number of binary 3d transition metal and iron nitrides, some of which still need to be synthesized, have been investigated by means of spin-polarized first principles band structure calculations ( TB-LMTO-ASA). The chemical bonding in all compounds has been clarified in detail through the analysis of total and local densities-of-states (DOS ) and crystal orbital Hamilton populations (COHP). The binary transition metal nitride set includes ScN, TiN, VN, CrN, MnN, FeN, CoN and NiN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 19 publications
5
99
0
2
Order By: Relevance
“…It is suggested that other unknown effects should be responsible for the extraordinarily larger lattice constant observed for FeN with NaCl structure. Eck et al [10] have estimated the equilibrium lattice constant for defected FeN and obtained a rather smaller a th . Up to date, no theoretical investigations on FeN film has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that other unknown effects should be responsible for the extraordinarily larger lattice constant observed for FeN with NaCl structure. Eck et al [10] have estimated the equilibrium lattice constant for defected FeN and obtained a rather smaller a th . Up to date, no theoretical investigations on FeN film has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It may therefore be, as suggested in Refs. [9,10], that the experimental NaCltype FeN with a=4.5Å is not in stable state due to unknown effects, such as the effect of the surface.…”
Section: Total Energy and Phase Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The GaON nanowires were assumed to be grown by the catalytic behavior of Ni or Co, which precipitated during ammonolysis due to the instability of their nitrides. 64) One-dimensional growth occurred because the metal precipitates obstruct isotropic two-dimensional growth of GaON in the hexagonal c-plane. The nanowire did not grow by VLS growth.…”
Section: )62)mentioning
confidence: 99%
“…The thermal stability of several types of metal nitrides and oxynitrides has been well studied. Transition metal nitrides gradually become unstable with an increase in their antibonding electronic contribution 15 . For example, a powder of α"-Fe 16 N 2 was prepared by ammonolysis of α-Fe powder at a very low temperature because of the thermally unstable chemical bonds between iron and nitrogen 16 .…”
Section: Introductionmentioning
confidence: 99%